The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1115/1.4025160
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Planetary Movement Parameters for Microhole Drilling by Micro-Electrical Discharge Machining

Abstract: Microholes are widely used in industrial products, such as engine nozzles and filters for biomedical industry. Electrical discharge machining (EDM) is one of processes to drill microholes in alloy with high aspect ratio. However, the achievable aspect ratio of a microhole by micro-EDM is limited. To improve the aspect ratio of a microhole drilled by micro-EDM, the planetary movement of electrode is applied during machining. It was found that the machining efficiency of microhole drilling can be further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Bamberg and Heamawatanachai investigated the effect of z-slicing, cylindrical slicing and z-spiralling during generation of circular micro features [9]. Similar studies have been carried out by Guo et al for generation of high aspect ratio micro holes [10]. Dave et al studied the application of orbital tool actuation on drilling of Inconel 718 and AISI 304 and reported that orbital parameters have an influence on material removal rate [11,12].…”
Section: Introductionmentioning
confidence: 91%
“…Bamberg and Heamawatanachai investigated the effect of z-slicing, cylindrical slicing and z-spiralling during generation of circular micro features [9]. Similar studies have been carried out by Guo et al for generation of high aspect ratio micro holes [10]. Dave et al studied the application of orbital tool actuation on drilling of Inconel 718 and AISI 304 and reported that orbital parameters have an influence on material removal rate [11,12].…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Bamberg and Heamawatanachi [12] assessed strategies like z-slicing, cylindrical slicing and z-spiraling for machining circular micro holes. The application of such tool actuation techniques has also been reported by Guo et al for creating high aspect ratio micro features [13]. Further, simultaneous application of tool orbiting as well as tool rotation has also been reported by Egashira et al and Ziada and Koshy for process improvement [14], [15].…”
Section: Introductionmentioning
confidence: 92%
“…Images of different types of electrodes (a) micro electrode [52], (b) solid copper electrode [83], (c) hollow copper electrodes [89] and bundled electrode [44] M. Kunieda et al (2000) developed multi-spark electrode and its circuit and found that this resulted in the increase of over all MRR and energy efficiency, tool wear ratio decreased and there was no significant improvement in SR [16]. The most significant change was development of WEDM where tool transformed into thin wire [15,84,26,20].…”
Section: Figurementioning
confidence: 99%